2008
DOI: 10.1093/nar/gkn683
|View full text |Cite
|
Sign up to set email alerts
|

PMAP: databases for analyzing proteolytic events and pathways

Abstract: The Proteolysis MAP (PMAP, http://www.proteolysis.org) is a user-friendly website intended to aid the scientific community in reasoning about proteolytic networks and pathways. PMAP is comprised of five databases, linked together in one environment. The foundation databases, ProteaseDB and SubstrateDB, are driven by an automated annotation pipeline that generates dynamic ‘Molecule Pages’, rich in molecular information. PMAP also contains two community annotated databases focused on function; CutDB has informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 29 publications
(26 reference statements)
1
32
0
Order By: Relevance
“…In general, less than 3% of aspartic acid cleavage sites are detected in the absence of exogenous caspase, suggesting little caspase activation. Several small-scale studies have previously identified a total of 37 and 68 substrates for caspase-2 and caspase-6, respectively (11,22,23). More than half of the previously reported caspase-2 substrates were found in our dataset (19 of the 37), and we identified 13 of 61 caspase-6 substrates reported in the CutDB database (cutdb.burnham.org/).…”
Section: Resultsmentioning
confidence: 58%
“…In general, less than 3% of aspartic acid cleavage sites are detected in the absence of exogenous caspase, suggesting little caspase activation. Several small-scale studies have previously identified a total of 37 and 68 substrates for caspase-2 and caspase-6, respectively (11,22,23). More than half of the previously reported caspase-2 substrates were found in our dataset (19 of the 37), and we identified 13 of 61 caspase-6 substrates reported in the CutDB database (cutdb.burnham.org/).…”
Section: Resultsmentioning
confidence: 58%
“…Consensus Disorder Prediction [34] discriminated ordered and disordered regions in the sequence (Fig. 5 and Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Each entry contains a proteolytic event relating a protease, a substrate, and a cleavage site and a description of the biological context. CutDB is part of the larger PMAP website, which also contains protease and substrate databases and tools for determining protease specificities and mapping signaling pathways (73). The termini-oriented protein function inferred database (TopFIND) is also open to user contributions (74).…”
Section: Methods For Enriching Protein N Termini-n-terminalmentioning
confidence: 99%